1968
DOI: 10.1002/oms.1210010309
|View full text |Cite
|
Sign up to set email alerts
|

The mass spectra of some cyclic ethers

Abstract: The mass spectral fragmentations of the saturated five-, six-and seven-membered ring ethers have been determined by studying their site-specifically deuterated analogues by both high and low-resolution mass spectrometry.The initial processes, governing the fragmentations of the cyclic ethers are shown to be identical with the well-known processes of linear nonbranched ethers, i.e. predominant a-fisson in the lower members and predominant carbon-oxygen fisson with charge retention on the carbon atom in the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The ferf-butyl cation, generated from ferf-butyl bromide or iodide, decomposes by loss of CH4 with randomization of Its hydrogens,181 while the formation of the C4H9+ ion Incorporating the Isopropyl group of 3,4-epoxymenthane requires migration of at least one hydrogen atom.182 Hydrogen scrambling before alkyl ion formation from pentaand hexamethylene oxide has been studied. 183 Ion structural studies have also been carried out on the CeHi3+ and CgHi?+ Ions from alkyl bromides and Io- Hydrogen rearrangements are also observed in the formation of various odd-electron ions from nonhydrocarbon sources.…”
Section: T H Imentioning
confidence: 99%
“…The ferf-butyl cation, generated from ferf-butyl bromide or iodide, decomposes by loss of CH4 with randomization of Its hydrogens,181 while the formation of the C4H9+ ion Incorporating the Isopropyl group of 3,4-epoxymenthane requires migration of at least one hydrogen atom.182 Hydrogen scrambling before alkyl ion formation from pentaand hexamethylene oxide has been studied. 183 Ion structural studies have also been carried out on the CeHi3+ and CgHi?+ Ions from alkyl bromides and Io- Hydrogen rearrangements are also observed in the formation of various odd-electron ions from nonhydrocarbon sources.…”
Section: T H Imentioning
confidence: 99%
“…was added. The mixture was heated to 50 "C under N,, a solution of tributyltin hydride (0.35 cm3, 1.3 mmol) in dry benzene (1 cm3) was added dropwise, and the mixture was stirred for 11 h. Analysis of the mixture by GCMS indicated that the sole product of cyclisation was thiepane l,l-di~xide,~, m/z 148 (M', 4), 131 (4), 120 (9, 83 (24), 67 (lo), 56 (60), 55 (loo), 41 (87) and 39 (32). Similar results were obtained on ultrasonification.…”
Section: 4-dihydro-2hmentioning
confidence: 99%
“…This result negates the earlier proposal (24), that they have an ethylene oxide (a) structure. Although some deuterium labelled tetrahydrofurans have been examined (25,26), it is still not possible to propose sound mechanisms for the formation of C 2 H 4 0 f ' daughter ions.…”
Section: Structure Assignments Of C2h40+' Fragmentmentioning
confidence: 99%